Diversité et enjeux territoriaux de la mise en art des espaces périphériques dans le monde - Sylvain Guyot; Grégoire Le Campion; Olivier Pissoat (Cybergeo, 2020)
The creation of art in peripheral spaces is a process of artistic colonization of rural and natural spaces in the world through site-specific artworks grouped in artistic sites, and initiated by a recurring triptych of stakeholders: artist, sponsor (elected official, institutional, artistic curator) and manager (local authority, artistic institution, protected space). Within peripheral spaces, such an artistic investment is often a costly process which responds to somewhat political priorities on the field. Artistic production therefore tends to create specific territories, between land privatization and supply of cultural public services. Several treatments in MCA (multiple correspondence analysis) and HAC (hierarchical ascending classification) are mobilized in this article to account for the diversity and the stakes of a database of more than 210 artistic sites described by about forty variables. The results of the CAH show that, on a global scale, the sites fall into three main categories: artwashing sculpture parks, territorial art of peripheral spaces and the eco-artistic fronts of project-works.